A cementing method suitable for CO2-EGS and its preparation method
Patent Information
- Application Number
- CN202610957921.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]现有技术中,常规G级油井水泥或地热固井水泥主要依赖硅酸盐熟料,其导热系数通常仅为~1.0 W/(m·K),远不能满足CO2-EGS的高效传热需求;同时碳化腐蚀速率在高温高压高浓度CO2环境下可达传统水泥的3~5倍,导致井筒窜漏风险显著增加
1.本发明的一种适用于二氧化碳增强型地热系统的固井水泥具有体系滤失量低、外加剂适应性好等特性,还具备导热系数高、抗CO2腐蚀、抗强度衰退和高温韧性好等特点。本发明一方面能够提高地热资源的取热效率,降低腐蚀性损伤,进而保证地热井固井质量及使用寿命。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of cementing materials technology for oil and gas field development, specifically to a cementing cement suitable for CO2-EGS and its preparation method. Background Technology
[0002] The carbon dioxide enhanced geothermal system (CO2-EGS) uses supercritical CO2 as the heat transfer medium and has advantages such as high heat transfer efficiency and good reservoir stimulation effect. However, it puts forward extremely demanding requirements on cementing: (1) it needs to have extremely high thermal conductivity to achieve efficient heat transfer; (2) it needs to resist the strength decay and permeability increase caused by CO2-induced carbonization corrosion under high temperature and high pressure; (3) it needs to resist the cracking of cement sheath caused by thermal-stress cycle and maintain the long-term sealing integrity of the wellbore.
[0003] In existing technologies, conventional G-grade oil well cement or geothermal cement mainly relies on silicate clinker, whose thermal conductivity is usually only ~1.0 W / (m·K), which is far from meeting the high-efficiency heat transfer requirements of CO2-EGS. At the same time, the carbonization corrosion rate can reach 3 to 5 times that of traditional cement in high-temperature, high-pressure, and high-concentration CO2 environments, leading to a significant increase in the risk of wellbore leakage. Although some studies have reported improving thermal conductivity by adding boron nitride, graphene, etc., these technologies generally have the following drawbacks: (1) poor dispersion of thermally conductive fillers, which cannot form a continuous thermally conductive network; (2) low effectiveness of single corrosion-resistant components and high cost. Therefore, it is urgent to develop a cementing system that simultaneously possesses high thermal conductivity, CO2 corrosion resistance, and crack resistance. Summary of the Invention
[0004] The purpose of this invention is to overcome the above-mentioned technical problems and provide a cementing material suitable for CO2-EGS and its preparation method, which has the properties of high thermal conductivity, CO2 corrosion resistance and crack resistance.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a cementing material suitable for CO2-EGS, comprising the following raw materials by weight percentage: Grade G oil well cement: 44-64.5%; High-temperature strength and anti-fading materials: 20-30%; Corrosion-resistant and thermally conductive materials: 15-25%; High-temperature toughness materials: 0.5-1.0%; And the following additives, calculated as a percentage of the total mass of the above raw materials: Dispersant: 0.2-0.6%; Water loss reducer: 1.0-3.0%; Retarder: 1.5-3.0%; The high-temperature strength-resistant material is a mixture of high-purity quartz powder, silica fume, and metakaolin. The corrosion-resistant thermally conductive material is a mixture of high thermal conductivity framework material, functional filler, self-responsive repair material, and corrosion-resistant reinforcing material. The high thermal conductivity framework material is a mixture of amino-modified hexagonal boron nitride, amino-modified silicon carbide whiskers, and modified expanded graphite. The functional filler is a mixture of lithium extraction slag under pressure with nitric acid, asbestos tailings, and calcium sulfoaluminate; The self-responsive repair material is KH2PO4 microcapsules; The corrosion-resistant reinforcing material is a mixture of fluorapatite-supported lanthanum aminotrimethylphosphonic acid chelate and nanoporous silica-supported active magnesium oxide powder; The high-temperature toughness material is a mixture of silane-modified basalt short-cut fibers and silane-modified short-cut carbon fibers.
[0006] Furthermore, the mass ratio of high-purity quartz powder, silica fume, and metakaolin in the high-temperature strength anti-fading material is 80:15:5; The mass ratio of high thermal conductivity skeleton material, functional filler, self-responsive repair material and corrosion-resistant reinforcing material in corrosion-resistant thermally conductive material is 6:7:3:4. The mass ratio of amino-modified hexagonal boron nitride, amino-modified silicon carbide whiskers, and modified expanded graphite in the high thermal conductivity framework material is 6:3:1. The mass ratio of nitric acid pressure lithium extraction slag, asbestos tailings and calcium sulfoaluminate in the functional packing is 6:2:1. In the corrosion-resistant reinforced material, the mass ratio of fluorapatite-supported lanthanum aminotrimethylphosphonate chelate to nanoporous silica-supported active magnesium oxide powder is 3:2. In the high-temperature toughness material, the mass ratio of silane-modified basalt short-cut fibers to silane-modified short-cut carbon fibers is 7:3.
[0007] Furthermore, the high-purity quartz powder has a particle size of 200–325 mesh and a SiO2 content of ≥98%; the silica fume has a D50 of 0.1–0.5 μm and a SiO2 content of ≥92%; and the metakaolin has a D50 of 1–10 μm, an Al2O3 content of ≥35%, and a SiO2 content of ≥50%.
[0008] Furthermore, the high thermal conductivity framework material is prepared using a method comprising the following steps: (1) Hexagonal boron nitride and silicon carbide whiskers that have been activated by ionosphere are dispersed in anhydrous ethanol at a mass ratio of 6:3, the solid content is controlled at 5%, and silane coupling agent KH550 accounting for 0.5% of the total mass of solid is added. The surface is modified by amination by mechanical stirring at 60°C for 2 h. After filtration, washing with ethanol, and vacuum drying at 80°C, amino-modified hexagonal boron nitride nanosheets and amino-modified silicon carbide whiskers are obtained. (2) Expanded graphite was ultrasonically dispersed in an 80% ethanol aqueous solution. Tetraethyl silicate was added at a mass ratio of 1:0.2 between expanded graphite and tetraethyl silicate. The pH was adjusted to 9-10 with ammonia. The mixture was stirred at 30°C for 60 min, washed with water and dried to obtain modified expanded graphite with a SiO2 shell coating on the surface. The thickness of the SiO2 shell was 10-50 nm. (3) Mix amino-modified hexagonal boron nitride nanosheets, amino-modified silicon carbide whiskers and modified expanded graphite in a V-type mixer at 30-60 rpm for 15-25 min to obtain a high thermal conductivity skeleton material.
[0009] 6. The cementing material according to claim 1, characterized in that the nitric acid pressure-extracted lithium slag contains SiO2 content >70%, Al2O3 content >20%, and the median particle size of the nitric acid pressure-extracted lithium slag is 1-20 μm; the asbestos tailings are heat-treated at 1200℃, wherein the SiO2 content is >45%, the MgO content is >30%, and the median particle size of the asbestos tailings is 1-20 μm.
[0010] Furthermore, the median particle size of the KH2PO4 microcapsules is 20-50 μm, and the capsule wall thickness is 1-5 μm.
[0011] KH2PO4 microcapsules were prepared using a method comprising the following steps: (1) Dissolve KH2PO4 in deionized water to form a solution A with a KH2PO4 saturation of 0.9, and obtain core material grains after spray drying; (2) Mix diethylaminoethyl methacrylate monomer (30% by mass of core material grains) and methylenebisacrylamide crosslinking agent (1.2 mol% by molar amount of diethylaminoethyl methacrylate monomer) evenly to obtain monomer phase; Sodium dodecyl sulfate was dissolved in deionized water to prepare an aqueous solution with a sodium dodecyl sulfate mass fraction of 0.2-0.5%. Initiator K2S2O8, accounting for 0.6% of the mass of the above diethylaminoethyl methacrylate monomer, was added, stirred and dissolved, and the pH was adjusted to 7.0 to obtain the aqueous phase. Add KH2PO4 to the aqueous phase to achieve a KH2PO4 saturation of 0.8-0.9. The monomer phase was slowly added to the aqueous phase at a volume ratio of 9:1. The mixture was dispersed at 800-1000 rpm for 10 min to emulsify and obtain solution B. Then the stirring speed was reduced to 350-450 rpm. (3) Add core material grains to solution B, the mass ratio of solution B to core material grains is 12:1, stir evenly, and purge with nitrogen for 30 min to remove oxygen; heat to 65°C and maintain the temperature for 4 h for polymerization reaction. (4) After the polymerization reaction is completed, the reaction system is cooled to room temperature, the microcapsules are separated by filtration, washed once with an aqueous solution of KH2PO4 with a saturation of 0.8-0.9, washed once with ethanol, and then vacuum dried at 45°C until the water content is <2% to obtain dried microcapsules; (5) Dissolve KH550 silane coupling agent in ethanol to prepare an ethanol solution with a KH550 mass fraction of 1.0%, add dried microcapsules at a liquid-to-solid ratio of 10 mL / g, stir at room temperature for 40 min for pretreatment, filter and separate, and vacuum dry at 50°C for 2 h to obtain pretreated microcapsules. (6) Disperse the pretreated microcapsules in anhydrous ethanol, control the mass ratio of microcapsules to anhydrous ethanol to be 1:9, and disperse evenly under mechanical stirring at 300 rpm to obtain a microcapsule dispersion. (7) Add 20% of the dry weight of the microcapsules of tetraethyl orthosilicate and 35% of the dry weight of the microcapsules of deionized water to the microcapsule dispersion, adjust the pH to 9-10 with ammonia water, and stir at 300-500 rpm for 100 min at 30°C to hydrolyze and condense the tetraethyl orthosilicate to generate silica and coat the surface of the microcapsules; after the reaction is completed, filter and separate, wash twice with ethanol, and vacuum dry at 45°C to obtain KH2PO4 microcapsules with silica coating.
[0012] Furthermore, the fluorapatite-supported lanthanum aminotrimethylphosphonate chelate was prepared using a method comprising the following steps: (1) Fluoroapatite with a particle size of 120 nm was dispersed in deionized water to prepare a suspension A with a fluoroapatite mass fraction of 8%; (2) Add aminotrimethylphosphonic acid, which accounts for 35% of the mass of fluorapatite, to suspension A, adjust the pH to 5-6, stir at room temperature for 30 min, and form suspension B; (3) Add lanthanum nitrate hexahydrate to suspension B in an amount equal to that of aminotrimethylphosphonic acid, heat to 60°C and stir for 2 h to form suspension C; (4) Filter the suspension C to separate the solid product; wash the solid product three times with deionized water, dry the washed solid product under vacuum at 80°C, and then pulverize it to 200 mesh to obtain fluorapatite-supported aminotrimethylphosphonic acid lanthanum chelate. Nanoporous silica-supported active magnesium oxide powder is prepared by a method including the following steps: (1) Disperse mesoporous silica with a pore size of 25 nm in anhydrous ethanol, and control the mass ratio of mesoporous silica to anhydrous ethanol to be 1:9 to obtain a mesoporous silica dispersion. (2) Add 30% of the mass of active magnesium oxide to the mesoporous silica dispersion to obtain a mixture, wherein the particle size of the active magnesium oxide is <20 nm. (3) The mixture was ultrasonically dispersed for 30 min to uniformly disperse the active magnesium oxide and load it onto the pores and surface of the mesoporous silica, thus obtaining a loaded suspension. (4) The loaded suspension is subjected to rotary evaporation to remove the anhydrous ethanol solvent, and the loaded solid powder is obtained; (5) Dry the solid powder in an inert atmosphere at 120°C to obtain nano-mesoporous silica-supported active magnesium oxide powder.
[0013] Furthermore, silane-modified basalt chopped fibers and silane-modified chopped carbon fibers were obtained by surface treatment of basalt chopped fibers and chopped carbon fibers with a mass fraction of 0.5% KH550 silane coupling agent, respectively; the basalt chopped fibers had a length of 3-6 mm and a diameter of 7-15 μm; the chopped carbon fibers had a length of 1-3 mm and a diameter of 5-10 μm.
[0014] Furthermore, the dispersant is sulfonated acetone-formaldehyde condensate; the water loss reducing agent is AMPS-type high-temperature resistant water loss reducing agent; and the retarder is a mixture of hydroxyethylidene diphosphonate and sodium gluconate in a mass ratio of 3:1.
[0015] The cementing method of this invention, which synergistically enhances thermal conductivity, CO2 corrosion resistance, crack resistance, and high-temperature toughness through the multi-component synergistic effect, is as follows.
[0016] 1. High-temperature strength anti-fading materials and functional fillers form a multi-level pozzolanic reaction system. Specifically, coarse-grained quartz powder provides a long-term high-temperature reaction framework, fine-grained silica fume and slag fill the capillaries and facilitate rapid reaction, while metakaolin and calcium sulfoaluminate in the functional fillers regulate the hydration products of the aluminum phase. Both the high-temperature strength anti-fading materials and the functional fillers provide active Si / Al sources, consuming Ca(OH)2 and reducing free Ca. 2+ It reduces the content of active calcium sources in the carbonization reaction. It can also regulate the Ca / Si ratio, promoting the formation of tobermorite, hard calcium silicate, and CASH gel, thus maintaining the dense structure of cement stone at high temperatures.
[0017] 2. In the high thermal conductivity framework material, amino-modified hexagonal boron nitride, amino-modified silicon carbide whiskers, and modified expanded graphite serve as micron-scale thermally conductive fillers. These three components complement each other through their complementary sheet-like and fibrous geometric morphologies, overlapping within the cement matrix to form continuous thermally conductive framework channels. Expanded graphite exhibits extremely high intrinsic in-plane thermal conductivity. Its surface-coated nanoscale (10-50 nm) SiO2 shell improves the interfacial compatibility between expanded graphite and cement hydration products, reduces interfacial defects and lowers interfacial thermal resistance, while simultaneously enhancing its dispersion stability in alkaline slurries. Silicon carbide whiskers, acting as one-dimensional thermally conductive bridging components, fill the voids between the sheet-like materials, extending the thermal conductivity pathway. Hexagonal boron nitride nanosheets combine high thermal conductivity with a favorable sheet-like morphology, further enriching the thermally conductive overlapping network. After surface modification with amination, hexagonal boron nitride and silicon carbide whiskers can form chemical bonds with cement hydration products due to their surface -NH2 active groups. The modified SiO2 shell on the surface of expanded graphite prevents direct reaction between graphite and alkaline substances in the cement paste, while also improving interfacial compatibility. Each component employs its own interface optimization strategy to stably integrate the thermally conductive framework into the cement matrix. The three micron-scale thermally conductive components work synergistically with the nanoscale SiO2 interface layer on the expanded graphite surface to construct a cross-scale thermal conductivity pathway from the nanoscale interface layer to the micron-scale framework, ultimately achieving a synergistic improvement in both thermal conductivity and mechanical properties.
[0018] 3. The nitric acid-pressurized lithium extraction slag and asbestos tailings in the functional filler are rich in active silica-alumina components (SiO2, Al2O3), which can undergo a secondary hydration reaction with the cement hydration product Ca(OH)2 to generate CSH gel with a low calcium-to-silicon ratio. This reduces the free Ca in the cement stone. 2+ The concentration of calcium sulfoaluminate is reduced, decreasing the substances that react with CO2 and inhibiting carbonation activity at its source. On the other hand, it refines the pore structure, cutting off the rapid diffusion channels of CO2. Simultaneously, calcium sulfoaluminate undergoes early hydration to form ettringite, and can generate a stable aluminate phase in a CO2 environment. These three factors work synergistically to improve the density of the cement matrix and reduce the penetration channels of corrosive media.
[0019] 4. The self-responsive repair material and the corrosion-resistant reinforcing material form a secondary dense phase MgKPO4·6H2O through a synergistic reinforcement mechanism, fundamentally hindering CO2 diffusion and blocking carbonization. Specifically, after the carbonization reaction occurs, the pH of the corroded area decreases, causing the self-responsive repair material to slowly release KH2PO4. The slowly released KH2PO4 reacts with the active magnesium oxide supported on nanoporous silica in the corrosion-resistant reinforcing material and the active MgO released from asbestos tailings in the functional filler, generating in situ MgKPO4·6H2O with low solubility and micro-expansion characteristics in the presence of water. This phase is chemically stable in a CO2 environment and can actively deposit at the bottlenecks of pores and microcracks, quickly sealing the channels and crack tips to form a dense protective network, significantly reducing the permeability of the cement matrix and fundamentally blocking further CO2 diffusion.
[0020] 5. Corrosion-resistant reinforcing materials further leverage multi-scale synergistic effects to improve the mechanical properties and corrosion resistance of the matrix. Specifically, fluorapatite itself has extremely strong acid resistance and can serve as an inert anti-corrosion skeleton to maintain the structural integrity of the cement stone; the loaded aminotrimethylphosphonic acid can chelate the Ca produced during cement hydration. 2+ This reduces the content of active reactants that can participate in the carbonization reaction in the system; chelated lanthanum ions (La 3+ It can interact with invading CO3 2- or HCO3 - A deposition reaction occurs, generating in-situ insoluble lanthanum carbonate (La2(CO3)3), further blocking ion migration channels. In the presence of water, the active magnesium oxide supported on nanoporous silica can react with invading CO2 to form micro-expandable magnesium carbonate (MgCO3), compensating for cement stone shrinkage. Simultaneously, it can react with KH2PO4 released from the self-responsive repair material to form MgKPO4·6H2O, creating a synergistic enhancement that also compensates for cement stone shrinkage. Furthermore, the mesoporous silica can participate in the secondary hydration of cement, refining the hydration product grains, reducing matrix porosity, and ultimately effectively blocking the penetration of CO2 and acidic formation media.
[0021] 6. High-temperature toughness materials construct a bridging network, which not only enhances the high-temperature crack resistance of cement stone but also connects high thermal conductivity skeleton materials to reduce thermal resistance and assist in the formation of a continuous high thermal conductivity skeleton. At the same time, the fibers first inhibit crack propagation during thermal stress cycling. After the cracks develop and introduce CO2 acidification medium to trigger a drop in pH, KH2PO4 microcapsules are released and react with MgO to generate hydration products that fill the cracks. Combined with corrosion-resistant reinforcing materials, the density of the matrix and chemical corrosion resistance are improved. The three work together to delay the intrusion of corrosive media and crack propagation, comprehensively ensuring the long-term sealing integrity of the cement ring under complex working conditions.
[0022] Through the synergistic effect of the above-mentioned multi-component and multi-gradient cement, the cement of this invention achieves improvements in thermal conductivity, compressive strength, CO2 corrosion resistance, and high-temperature toughness.
[0023] A second aspect of the present invention provides a method for preparing cementing suitable for CO2-EGS, comprising: Step 1: Weigh the high thermal conductivity skeleton material, functional filler, self-responsive repair material, and corrosion-resistant reinforcing material according to the proportions. First, add the components of the functional filler (nitric acid pressure lithium extraction slag, asbestos tailings, and calcium sulfoaluminate) to a dry powder mixer and mix at 300-500 rpm for 5-15 minutes until homogeneous. Then, add the self-responsive repair material, corrosion-resistant reinforcing material, and high thermal conductivity skeleton material in sequence and mix at 300-500 rpm for 3-8 minutes until homogeneous to obtain the corrosion-resistant thermally conductive material. Step 2: Weigh out G-grade oil well cement, high-temperature strength anti-fading material, corrosion-resistant thermal conductive material and high-temperature toughness material, add G-grade oil well cement, high-temperature strength anti-fading material, corrosion-resistant thermal conductive material and high-temperature toughness material into a dry powder mixer, and stir at 200-400 rpm for 3-8 minutes to obtain dry mixture; Step 3: Weigh the mixing water, add the dispersant, water loss reducer, and retarder to the mixing water in sequence, mix well to form a liquid; Step 4: Mix the dry and liquid materials evenly to obtain cementing material suitable for CO2-EGS.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The cementing material for carbon dioxide-enhanced geothermal systems of the present invention has the characteristics of low system filtration loss and good adaptability to admixtures, as well as high thermal conductivity, resistance to CO2 corrosion, resistance to strength degradation, and good high-temperature toughness. On the one hand, the present invention can improve the heat extraction efficiency of geothermal resources and reduce corrosive damage, thereby ensuring the cementing quality and service life of geothermal wells.
[0025] 2. This invention constructs a multi-stage pozzolanic reaction system using high-temperature strength-resistant materials and functional fillers, consuming Ca(OH)2 and reducing free Ca. 2+ The content reduces the active calcium source of carbonization reaction at the source; at the same time, it promotes the formation of tobermorite, hard silicate and CASH gel, so that the cement stone maintains a dense structure at high temperature and effectively resists strength decline and permeability increase.
[0026] 3. The high thermal conductivity skeleton material of the present invention forms a continuous thermally conductive network through the geometric complementary overlap of sheet-like boron nitride, fibrous silicon carbide whiskers and layered expanded graphite; the nano-SiO2 shell on the surface of expanded graphite improves the interfacial bonding and reduces thermal resistance, and the amylation modification enhances the chemical bonding between the skeleton and the cement matrix, thus constructing a cross-scale thermal conductivity pathway and achieving a synergistic improvement in thermal conductivity and mechanical properties.
[0027] 4. The self-responsive repair material of this invention slowly releases KH2PO4 when the pH of the carbonized region decreases, and reacts with active MgO in situ to form insoluble and stable MgKPO4·6H2O, actively sealing the pores and crack tips; the corrosion-resistant reinforcing material uses a fluorapatite inert framework and aminotrimethylphosphonic acid chelate to chelate Ca... 2+ The cement stone possesses dual corrosion resistance capabilities, including active defense and passive barrier, through a combination of multiple mechanisms such as lanthanum ion precipitation to block pores, mesoporous silica to refine grains, and active magnesium oxide to compensate for shrinkage.
[0028] 5. The high-temperature toughness material of this invention constructs a bridging network, which improves the crack resistance and toughness of cement stone and assists in the connection of the thermally conductive skeleton; in conjunction with self-responsive repair and corrosion resistance enhancement, it ensures the long-term sealing integrity of the cement ring under the coupled conditions of heat-stress-corrosion.
[0029] 6. This invention uses industrial solid waste as the main raw material, which is low in cost, simple in process, and has good adaptability to additives. It has both economic and environmental benefits and is easy to promote and apply on site. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0031] In this embodiment of the invention, the mass ratio of high-purity quartz powder, silica fume, and metakaolin in the high-temperature strength anti-fading material is 80:15:5; The mass ratio of high thermal conductivity skeleton material, functional filler, self-responsive repair material and corrosion-resistant reinforcing material in corrosion-resistant thermally conductive material is 6:7:3:4. The mass ratio of amino-modified hexagonal boron nitride, amino-modified silicon carbide whiskers, and modified expanded graphite in the high thermal conductivity framework material is 6:3:1. The mass ratio of nitric acid pressure lithium extraction slag, asbestos tailings and calcium sulfoaluminate in the functional packing is 6:2:1. In the corrosion-resistant reinforced material, the mass ratio of fluorapatite-supported lanthanum aminotrimethylphosphonate chelate to nanoporous silica-supported active magnesium oxide powder is 3:2. In the high-temperature toughness material, the mass ratio of silane-modified basalt short-cut fibers to silane-modified short-cut carbon fibers is 7:3.
[0032] The particle size of high-purity quartz powder is 200–325 mesh, and the SiO2 content is ≥98%; the D50 of silica fume is 0.1–0.5 μm, and the SiO2 content is ≥92%; the D50 of metakaolin is 1–10 μm, the Al2O3 content is ≥35%, and the SiO2 content is ≥50%.
[0033] The high thermal conductivity framework material is prepared by a method including the following steps: (1) Hexagonal boron nitride and silicon carbide whiskers that have been activated by ionosphere are dispersed in anhydrous ethanol at a mass ratio of 6:3, the solid content is controlled at 5%, and silane coupling agent KH550 accounting for 0.5% of the total mass of solid is added. The surface is modified by amination by mechanical stirring at 60°C for 2 h. After filtration, washing with ethanol, and vacuum drying at 80°C, amino-modified hexagonal boron nitride nanosheets and amino-modified silicon carbide whiskers are obtained. (2) Expanded graphite was ultrasonically dispersed in an 80% ethanol aqueous solution. Tetraethyl silicate was added at a mass ratio of 1:0.2 between expanded graphite and tetraethyl silicate. The pH was adjusted to 9-10 with ammonia. The mixture was stirred at 30°C for 60 min, washed with water and dried to obtain modified expanded graphite with a SiO2 shell coating on the surface. The thickness of the SiO2 shell was 10-50 nm. (3) Mix amino-modified hexagonal boron nitride nanosheets, amino-modified silicon carbide whiskers and modified expanded graphite in a V-type mixer at 30-60 rpm for 15-25 min to obtain a high thermal conductivity skeleton material.
[0034] Hexagonal boron nitride sheets have a diameter of 5-20 μm and a thickness of 0.1-0.5 μm; silicon carbide whiskers have a length of 10-50 μm and a diameter of 0.2-1 μm; expanded graphite has a thickness of 3-10 μm and a surface diameter of 20-200 μm.
[0035] The above-mentioned plasma activation treatment is existing technology, so it will not be described in detail.
[0036] The lithium extraction slag from nitric acid pressure extraction contains >70% SiO2 and >20% Al2O3, with a median particle size of 1-20 μm; the asbestos tailings are heat-treated at 1200℃, containing >45% SiO2 and >30% MgO, with a median particle size of 1-20 μm; and the calcium sulfoaluminate is a commercially available product with an effective content >90% and a median particle size of 5-10 μm.
[0037] The median particle size of KH2PO4 microcapsules is 20-50 μm, and the capsule wall thickness is 1-5 μm.
[0038] KH2PO4 microcapsules were prepared using a method comprising the following steps: (1) KH2PO4 is dissolved in deionized water to form a solution A with a KH2PO4 saturation of 0.9. After spray drying (inlet 180℃ / outlet 80℃), the core material grains are obtained. (2) Mix diethylaminoethyl methacrylate monomer (30% by mass of core material grains) and methylenebisacrylamide crosslinking agent (1.2 mol% by molar amount of diethylaminoethyl methacrylate monomer) evenly to obtain monomer phase; Sodium dodecyl sulfate was dissolved in deionized water to prepare an aqueous solution with a sodium dodecyl sulfate mass fraction of 0.2-0.5%. Initiator K2S2O8, accounting for 0.6% of the mass of the above diethylaminoethyl methacrylate monomer, was added, stirred and dissolved, and the pH was adjusted to 7.0 to obtain the aqueous phase. Add KH2PO4 to the aqueous phase to achieve a KH2PO4 saturation of 0.8-0.9. The monomer phase was slowly added to the aqueous phase at a volume ratio of 9:1. The mixture was dispersed at 800-1000 rpm for 10 min to emulsify and obtain solution B. Then the stirring speed was reduced to 350-450 rpm. (3) Add core material grains to solution B, the mass ratio of solution B to core material grains is 12:1, stir evenly, and purge with nitrogen for 30 min to remove oxygen; heat to 65°C and maintain the temperature for 4 h for polymerization reaction. (4) After the polymerization reaction is completed, the reaction system is cooled to room temperature, the microcapsules are separated by filtration, washed once with an aqueous solution of KH2PO4 with a saturation of 0.8-0.9, washed once with ethanol, and then vacuum dried at 45°C until the water content is <2% to obtain dried microcapsules; (5) Dissolve KH550 silane coupling agent in ethanol to prepare an ethanol solution with a KH550 mass fraction of 1.0%, add dried microcapsules at a liquid-to-solid ratio of 10 mL / g, stir at room temperature for 40 min for pretreatment, filter and separate, and vacuum dry at 50°C for 2 h to obtain pretreated microcapsules. (6) Disperse the pretreated microcapsules in anhydrous ethanol, control the mass ratio of microcapsules to anhydrous ethanol to be 1:9, and disperse evenly under mechanical stirring at 300 rpm to obtain a microcapsule dispersion. (7) Add 20% of the dry weight of the microcapsules of tetraethyl orthosilicate and 35% of the dry weight of the microcapsules of deionized water to the microcapsule dispersion, adjust the pH to 9-10 with ammonia water, and stir at 300-500 rpm for 100 min at 30°C to hydrolyze and condense the tetraethyl orthosilicate to generate silica and coat the surface of the microcapsules; after the reaction is completed, filter and separate, wash twice with ethanol, and vacuum dry at 45°C to obtain KH2PO4 microcapsules with silica coating.
[0039] The fluorapatite-supported lanthanum aminotrimethylphosphonate chelate was prepared by a method comprising the following steps: (1) Fluoroapatite with a particle size of 120 nm was dispersed in deionized water to prepare a suspension A with a fluoroapatite mass fraction of 8%; (2) Add aminotrimethylphosphonic acid, which accounts for 35% of the mass of fluorapatite, to suspension A, adjust the pH to 5-6, stir at room temperature for 30 min, and form suspension B; (3) Add lanthanum nitrate hexahydrate to suspension B in an amount equal to that of aminotrimethylphosphonic acid, heat to 60°C and stir for 2 h to form suspension C; (4) Filter the suspension C to separate the solid product; wash the solid product three times with deionized water, dry the washed solid product under vacuum at 80°C, and then pulverize it to 200 mesh to obtain fluorapatite-supported aminotrimethylphosphonic acid lanthanum chelate. Nanoporous silica-supported active magnesium oxide powder is prepared by a method including the following steps: (1) Disperse mesoporous silica with a pore size of 25 nm in anhydrous ethanol, and control the mass ratio of mesoporous silica to anhydrous ethanol to be 1:9 to obtain a mesoporous silica dispersion. (2) Add 30% of the mass of active magnesium oxide to the mesoporous silica dispersion to obtain a mixture, wherein the particle size of the active magnesium oxide is <20 nm. (3) The mixture was ultrasonically dispersed for 30 min to uniformly disperse the active magnesium oxide and load it onto the pores and surface of the mesoporous silica, thus obtaining a loaded suspension. (4) The loaded suspension is subjected to rotary evaporation to remove the anhydrous ethanol solvent, and the loaded solid powder is obtained; (5) Dry the solid powder in an inert atmosphere at 120°C to obtain nano-mesoporous silica-supported active magnesium oxide powder.
[0040] Silane-modified basalt chopped fibers and silane-modified chopped carbon fibers were obtained by surface treatment of basalt chopped fibers and chopped carbon fibers with a mass fraction of 0.5% KH550 silane coupling agent, respectively; the basalt chopped fibers had a length of 3-6 mm and a diameter of 7-15 μm; the chopped carbon fibers had a length of 1-3 mm and a diameter of 5-10 μm.
[0041] The dispersant is sulfonated acetone-formaldehyde condensate; the water loss reducing agent is AMPS-type high-temperature resistant water loss reducing agent; the retarder is a mixture of hydroxyethylidene diphosphonate and sodium gluconate in a mass ratio of 3:1.
[0042] Example 1, as a preferred embodiment of the present invention, provides a cementing material suitable for CO2-EGS, the composition of which is as follows: Grade G oil well cement: 44%; High-temperature strength anti-fading materials: 30%; Corrosion-resistant thermally conductive materials: 25%; High-temperature toughness materials: 1.0%; And the following additives, calculated as a percentage of the total mass of the above raw materials: Dispersant: 0.6%; Water loss reducer: 3.0%; Retarder: 3.0%.
[0043] The preparation method of cementing cement is as follows: Step 1: Weigh the high thermal conductivity skeleton material, functional filler, self-responsive repair material, and corrosion-resistant reinforcing material according to the proportions. First, add the components of the functional filler (nitric acid pressure lithium extraction slag, asbestos tailings, and calcium sulfoaluminate) to a dry powder mixer and mix at 400 rpm for 10 minutes until homogeneous. Then, add the self-responsive repair material, corrosion-resistant reinforcing material, and high thermal conductivity skeleton material in sequence and mix at 400 rpm for 5 minutes until homogeneous to obtain the corrosion-resistant thermally conductive material. Step 2: Weigh out G-grade oil well cement, high-temperature strength anti-fading material, corrosion-resistant thermal conductive material and high-temperature toughness material, add G-grade oil well cement, high-temperature strength anti-fading material, corrosion-resistant thermal conductive material and high-temperature toughness material into a dry powder mixer, stir at 300 rpm for 5 minutes to obtain dry mixture; Step 3: Weigh the mixing water, add the dispersant, water loss reducer, and retarder to the mixing water in sequence, mix well to form a liquid; Step 4: Mix the dry and liquid materials evenly to obtain cementing material suitable for CO2-EGS.
[0044] Example 2, as a preferred embodiment of the present invention, provides a cementing material suitable for CO2-EGS, the composition of which is as follows: Grade G oil well cement: 54.2%; High-temperature strength and anti-fading materials: 25%; Corrosion-resistant thermally conductive materials: 20%; High-temperature toughness material: 0.8%; And the following additives, calculated as a percentage of the total mass of the above raw materials: Dispersant: 0.4%; Water loss reducer: 2.0%; Retarder: 2.0%.
[0045] The preparation method is the same as in Example 1.
[0046] Example 3, as a preferred embodiment of the present invention, provides a cementing material suitable for CO2-EGS, the composition of which is as follows: Grade G oil well cement: 64.5%; High-temperature strength and anti-fading materials: 20%; Corrosion-resistant thermally conductive materials: 15%; High-temperature toughness material 0.5%; And the following additives, calculated as a percentage of the total mass of the above raw materials: Dispersant: 0.2%; Water loss reducer: 1.0%; Retarder: 1.5%.
[0047] The preparation method is the same as in Example 1.
[0048] Comparative Example 1 differs from Example 1 in that it does not contain high-temperature strength anti-degradation materials, while the remaining components, proportions, and preparation methods remain unchanged, and the missing parts are made up with G-grade oil well cement.
[0049] Comparative Example 2 differs from Example 1 in that the corrosion-resistant thermally conductive material does not contain a high thermal conductivity skeleton material, while the remaining components, proportions, and preparation methods remain unchanged, and the missing parts are filled by G-grade oil well cement.
[0050] Comparative Example 3 differs from Example 1 in that the corrosion-resistant thermal conductive material does not contain self-responsive repair material, while the remaining components, proportions, and preparation methods remain unchanged, and the missing parts are filled with G-grade oil well cement.
[0051] Comparative Example 4 differs from Example 1 in that it does not contain corrosion-resistant reinforcing materials, while the remaining components, proportions, and preparation methods remain unchanged, and the missing parts are filled with G-grade oil well cement.
[0052] Comparative Example 5 differs from Example 1 in that it does not contain high-temperature toughness material, while the other components, proportions and preparation methods remain unchanged, and the missing parts are made up with G-grade oil well cement.
[0053] For the test example, referring to GB / T19139 Oil Well Cement Test Method, the amount of mixing water in the above cementing cement preparation method was determined according to the water-to-solid ratio of 0.5. Then, the cement slurry engineering performance of the cementing cement system prepared in Examples 1-3 was tested at 150℃. The results are shown in Table 1.
[0054] Cement stone samples obtained from the cementing systems of each embodiment and comparative example were placed in a high-temperature, high-pressure corrosion reactor and placed in a high-temperature, high-pressure, gaseous supercritical CO2 environment containing water vapor. The curing temperature was 180°C, the CO2 pressure was 5 MPa, and the total pressure was 10 MPa (compensated by N2 partial pressure). The curing periods were 7 days and 28 days. The compressive strength, permeability, and elastic modulus of the cement stone were tested.
[0055] The compressive strength of the cured samples was tested using an NYSQ-2017 pressure testing machine; the permeability of each cement slurry sample was measured according to standard SY / T 6466-2000 "Evaluation Method for High Temperature Resistance of Oil Well Cement Stone"; and the thermal conductivity of the cement stone was tested using a DRE-2C thermal conductivity meter employing the transient plane heat source method. The test results are shown in Table 2.
[0056] Table 1. Test Results of Cement Slurry Engineering Performance
[0057] Table 2 Test results of cement stone
[0058] According to the experimental data in Table 1, the water loss of the cement slurry system prepared in Examples 1-3 is less than 40 ml; its fluidity and initial consistency meet the construction requirements, the thickening time is controllable, and all engineering performances are good.
[0059] As shown in Table 2, after a certain corrosion period, the cement stone of Examples 1-3 exhibits a 7-day compressive strength greater than 36 MPa, a 28-day compressive strength that shows no decline and is greater than 40 MPa, a 28-day permeability less than 0.03 mD, an elastic modulus less than 8.0 GPa, and a thermal conductivity greater than 1.4 W / (m·K). This indicates that the cementing system of the present invention possesses excellent high-temperature resistance, corrosion resistance, high thermal conductivity, and high toughness. Compared with Example 1, the data from Comparative Examples 1-5 show that the present invention does not rely on a single material to improve a particular performance, but rather achieves comprehensive performance enhancement through the synergistic effect of multiple components, multiple scales, and multiple mechanisms, enabling the cement stone to maintain a dense, high-strength, high-toughness, and high-thermal-conductivity structure even in high-temperature, high-pressure, CO2, and thermal stress coupled environments.
[0060] In summary, the present invention can meet the comprehensive requirements of carbon dioxide enhanced geothermal systems for cementing cement in terms of high thermal conductivity, corrosion resistance, high temperature resistance, crack resistance, and long-term sealing integrity.
[0061] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.
Claims
1. A cementing agent suitable for CO2-EGS, characterized in that, Includes the following raw materials by weight percentage: Grade G oil well cement: 44-64.5%; High-temperature strength and anti-fading materials: 20-30%; Corrosion-resistant and thermally conductive materials: 15-25%; High-temperature toughness materials: 0.5-1.0%; And the following additives, calculated as a percentage of the total mass of the above raw materials: Dispersant: 0.2-0.6%; Water loss reducer: 1.0-3.0%; Retarder: 1.5-3.0%; The high-temperature strength-resistant material is a mixture of high-purity quartz powder, silica fume, and metakaolin. The corrosion-resistant thermally conductive material is a mixture of high thermal conductivity framework material, functional filler, self-responsive repair material, and corrosion-resistant reinforcing material. The high thermal conductivity framework material is a mixture of amino-modified hexagonal boron nitride, amino-modified silicon carbide whiskers, and modified expanded graphite. The functional filler is a mixture of lithium extraction slag under pressure with nitric acid, asbestos tailings, and calcium sulfoaluminate; The self-responsive repair material is KH2PO4 microcapsules; The corrosion-resistant reinforcing material is a mixture of fluorapatite-supported lanthanum aminotrimethylphosphonic acid chelate and nanoporous silica-supported active magnesium oxide powder; The high-temperature toughness material is a mixture of silane-modified basalt short-cut fibers and silane-modified short-cut carbon fibers.
2. The cementing cement according to claim 1, characterized in that, The mass ratio of high-purity quartz powder, silica fume, and metakaolin in the high-temperature strength anti-fading material is 80:15:5; The mass ratio of high thermal conductivity skeleton material, functional filler, self-responsive repair material and corrosion-resistant reinforcing material in corrosion-resistant thermally conductive material is 6:7:3:
4. The mass ratio of amino-modified hexagonal boron nitride, amino-modified silicon carbide whiskers, and modified expanded graphite in the high thermal conductivity framework material is 6:3:
1. The mass ratio of nitric acid pressure lithium extraction slag, asbestos tailings and calcium sulfoaluminate in the functional packing is 6:2:
1. In the corrosion-resistant reinforced material, the mass ratio of fluorapatite-supported lanthanum aminotrimethylphosphonate chelate to nanoporous silica-supported active magnesium oxide powder is 3:
2. In the high-temperature toughness material, the mass ratio of silane-modified basalt short-cut fibers to silane-modified short-cut carbon fibers is 7:
3.
3. The cementing cement according to claim 1, characterized in that, The particle size of high-purity quartz powder is 200–325 mesh, and the SiO2 content is ≥98%; the D50 of silica fume is 0.1–0.5 μm, and the SiO2 content is ≥92%; the D50 of metakaolin is 1–10 μm, the Al2O3 content is ≥35%, and the SiO2 content is ≥50%.
4. The cementing cement according to claim 1, characterized in that, The high thermal conductivity framework material is prepared by a method including the following steps: (1) Hexagonal boron nitride and silicon carbide whiskers that have been activated by ionosphere are dispersed in anhydrous ethanol at a mass ratio of 6:3, the solid content is controlled at 5%, and silane coupling agent KH550 accounting for 0.5% of the total mass of solid is added. The surface is modified by amination by mechanical stirring at 60°C for 2 h. After filtration, washing with ethanol, and vacuum drying at 80°C, amino-modified hexagonal boron nitride nanosheets and amino-modified silicon carbide whiskers are obtained. (2) Expanded graphite was ultrasonically dispersed in an 80% ethanol aqueous solution. Tetraethyl silicate was added at a mass ratio of 1:0.2 between expanded graphite and tetraethyl silicate. The pH was adjusted to 9-10 with ammonia. The mixture was stirred at 30°C for 60 min, washed with water and dried to obtain modified expanded graphite with a SiO2 shell coating on the surface. The thickness of the SiO2 shell was 10-50 nm. (3) Mix amino-modified hexagonal boron nitride nanosheets, amino-modified silicon carbide whiskers and modified expanded graphite in a V-type mixer at 30-60 rpm for 15-25 min to obtain a high thermal conductivity skeleton material.
5. The cementing cement according to claim 1, characterized in that, The lithium extraction slag produced by nitric acid pressure extraction has a SiO2 content of >70%, an Al2O3 content of >20%, and a median particle size of 1-20 μm; the asbestos tailings, after heat treatment at 1200℃, have a SiO2 content of >45%, an MgO content of >30%, and a median particle size of 1-20 μm.
6. The cementing cement according to claim 1, characterized in that, The median particle size of KH2PO4 microcapsules is 20-50 μm, and the capsule wall thickness is 1-5 μm. KH2PO4 microcapsules were prepared using a method comprising the following steps: (1) Dissolve KH2PO4 in deionized water to form a solution A with a KH2PO4 saturation of 0.9, and obtain core material grains after spray drying; (2) Mix diethylaminoethyl methacrylate monomer (30% by mass of core material grains) and methylenebisacrylamide crosslinking agent (1.2 mol% by molar amount of diethylaminoethyl methacrylate monomer) evenly to obtain monomer phase; Sodium dodecyl sulfate was dissolved in deionized water to prepare an aqueous solution with a sodium dodecyl sulfate mass fraction of 0.2-0.5%. Initiator K2S2O8, accounting for 0.6% of the mass of the above diethylaminoethyl methacrylate monomer, was added, stirred and dissolved, and the pH was adjusted to 7.0 to obtain the aqueous phase. Add KH2PO4 to the aqueous phase to achieve a KH2PO4 saturation of 0.8-0.
9. The monomer phase was slowly added to the aqueous phase at a volume ratio of 9:
1. The mixture was dispersed at 800-1000 rpm for 10 minutes to emulsify and obtain solution B. Then the stirring speed was reduced to 350-450 rpm. (3) Add core material grains to solution B, the mass ratio of solution B to core material grains is 12:1, stir evenly, and purge with nitrogen for 30 min to remove oxygen; heat to 65°C and maintain the temperature for 4 h for polymerization reaction. (4) After the polymerization reaction is completed, the reaction system is cooled to room temperature, the microcapsules are separated by filtration, washed once with an aqueous solution of KH2PO4 with a saturation of 0.8-0.9, washed once with ethanol, and then vacuum dried at 45°C until the water content is <2% to obtain dried microcapsules; (5) Dissolve KH550 silane coupling agent in ethanol to prepare an ethanol solution with a KH550 mass fraction of 1.0%, add dried microcapsules at a liquid-to-solid ratio of 10 mL / g, stir at room temperature for 40 min for pretreatment, filter and separate, and vacuum dry at 50°C for 2 h to obtain pretreated microcapsules. (6) Disperse the pretreated microcapsules in anhydrous ethanol, control the mass ratio of microcapsules to anhydrous ethanol to be 1:9, and disperse evenly under mechanical stirring at 300 rpm to obtain a microcapsule dispersion. (7) Add 20% of the dry weight of the microcapsules of tetraethyl orthosilicate and 35% of the dry weight of the microcapsules of deionized water to the microcapsule dispersion, adjust the pH to 9-10 with ammonia water, and stir at 300-500 rpm for 100 min at 30°C to hydrolyze and condense the tetraethyl orthosilicate to generate silica and coat the surface of the microcapsules; after the reaction is completed, filter and separate, wash twice with ethanol, and vacuum dry at 45°C to obtain KH2PO4 microcapsules with silica coating.
7. The cementing cement according to claim 1, characterized in that, The fluorapatite-supported lanthanum aminotrimethylphosphonate chelate was prepared by a method comprising the following steps: (1) Fluorapatite with a particle size of 120 nm was dispersed in deionized water to prepare a suspension A with a fluorapatite mass fraction of 8%. (2) Add aminotrimethylphosphonic acid, which accounts for 35% of the mass of fluorapatite, to suspension A, adjust the pH to 5-6, stir at room temperature for 30 min, and form suspension B; (3) Add lanthanum nitrate hexahydrate to suspension B in an amount equal to that of aminotrimethylphosphonic acid, heat to 60°C and stir for 2 h to form suspension C; (4) Filter the suspension C to separate the solid product; wash the solid product three times with deionized water, dry the washed solid product under vacuum at 80°C, and then pulverize it to 200 mesh to obtain fluorapatite-supported aminotrimethylphosphonic acid lanthanum chelate. Nanoporous silica-supported active magnesium oxide powder is prepared by a method including the following steps: (1) Disperse mesoporous silica with a pore size of 25 nm in anhydrous ethanol, and control the mass ratio of mesoporous silica to anhydrous ethanol to be 1:9 to obtain a mesoporous silica dispersion. (2) Add 30% of the mass of active magnesium oxide to the mesoporous silica dispersion to obtain a mixture, wherein the particle size of the active magnesium oxide is <20 nm. (3) The mixture was ultrasonically dispersed for 30 min to uniformly disperse the active magnesium oxide and load it onto the pores and surface of the mesoporous silica, thus obtaining a loaded suspension. (4) The loaded suspension is subjected to rotary evaporation to remove the anhydrous ethanol solvent, and the loaded solid powder is obtained; (5) Dry the solid powder in an inert atmosphere at 120°C to obtain nano-mesoporous silica-supported active magnesium oxide powder.
8. The cementing cement according to claim 1, characterized in that, Silane-modified basalt chopped fibers and silane-modified chopped carbon fibers were obtained by surface treatment of basalt chopped fibers and chopped carbon fibers with a mass fraction of 0.5% KH550 silane coupling agent, respectively; the basalt chopped fibers had a length of 3-6 mm and a diameter of 7-15 μm; the chopped carbon fibers had a length of 1-3 mm and a diameter of 5-10 μm.
9. The cementing cement according to claim 1, characterized in that, The dispersant is sulfonated acetone-formaldehyde condensate; the water loss reducing agent is AMPS-type high-temperature resistant water loss reducing agent; the retarder is a mixture of hydroxyethylidene diphosphonate and sodium gluconate in a mass ratio of 3:
1.
10. A method for preparing cementing as described in any one of claims 1-9, characterized in that, include: Step 1: Weigh the high thermal conductivity skeleton material, functional filler, self-responsive repair material, and corrosion-resistant reinforcing material according to the proportions. First, add the components of the functional filler (nitric acid pressure lithium extraction slag, asbestos tailings, and calcium sulfoaluminate) to a dry powder mixer and mix at 300-500 rpm for 5-15 minutes until homogeneous. Then, add the self-responsive repair material, corrosion-resistant reinforcing material, and high thermal conductivity skeleton material in sequence and mix at 300-500 rpm for 3-8 minutes until homogeneous to obtain the corrosion-resistant thermally conductive material. Step 2: Weigh out G-grade oil well cement, high-temperature strength anti-fading material, corrosion-resistant thermal conductive material and high-temperature toughness material, add G-grade oil well cement, high-temperature strength anti-fading material, corrosion-resistant thermal conductive material and high-temperature toughness material into a dry powder mixer, and stir at 200-400 rpm for 3-8 minutes to obtain dry mixture; Step 3: Weigh the mixing water, add the dispersant, water loss reducer, and retarder to the mixing water in sequence, mix well to form a liquid; Step 4: Mix the dry and liquid materials evenly to obtain cementing material suitable for CO2-EGS.